A new species of Tricorythodes Ulmer (Ephemeroptera: Leptohyphidae) from Uruguay - Emmerich, Daniel; Molineri, Carlos (Zootaxa, 2020)
A new species of Tricorythodes Ulmer (Ephemeroptera: Leptohyphidae) from Uruguay is described and illustrated based on nymphs and adults. Tricorythodes biluhue sp. nov. is related to T. arequita Traver, T. mirca Molineri, T. sallesi Dias, Cabette & De Sousa, and T. tragoedia Souto, Angeli & Salles. The adults of these species are similar (share body color patterns formed by irregularly distributed pigments, while nymphs and adults present subapical blackish marks on tibiae). The nymphs of the new species present a spine on the inner margin of superlingua; operculate gills with a clear paler anterolateral area; and fore tarsal claw with 10–13 marginal denticles and with 0–1 + 1 submarginal denticles. This species has a wide distribution in Uruguay and was found in small streams with stony substrate and thick sand. Additional records for T. arequita Traver in Uruguay are also provided.